ESSAY WRITING COMPREHENSION AMONG 3RD SEMESTER EFL STUDENTS OF ENGLISH DEPARTMENT - Muhammad Yasminto (POJOK GURU: Jurnal Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to explore essay writing comprehension among third-semester English as a Foreign Language (EFL) students of the English Department. A qualitative phenomenology design was employed to gain an in-depth understanding of students’ comprehension of essay writing principles. The participants were selected through purposive sampling and consisted of third-semester students enrolled in an essay writing course. Data were collected through students’ written essays, semi-structured interviews, and classroom observations. The data were analyzed using thematic analysis to identify recurring patterns related to students’ essay writing comprehension. The findings revealed that students demonstrated a basic understanding of the general structure of an academic essay, including the introduction, body paragraphs, and conclusion. However, their comprehension of key aspects such as thesis statement formulation, coherence and cohesion, idea development, and effective language use was limited. Many students experienced difficulties in developing clear and focused thesis statements, organizing ideas logically, and providing sufficient supporting details. Language-related challenges, including grammatical inaccuracies and limited vocabulary, also affected the clarity and coherence of students’ essays. These findings indicate a gap between students’ structural awareness and their deeper conceptual understanding of essay writing. The study suggests that more focused instructional strategies emphasizing rhetorical awareness, discourse-level organization, and guided writing practice are necessary to enhance EFL students’ essay writing comprehension at the tertiary level